Biomass reinforced graphene oxide solid/liquid phase membrane extraction for the measurement of Pb(II) in food samples. (15th December 2018) - Wang, Jing; Liu, Manshun; Zhang, Liang; Zhang, Tianshu; Yue, Tianli; Li, Zhonghong; Hu, Na; Suo, Yourui; Wang, Jianlong
Highlights: Integrated solid/liquid phase extraction mode for Pb(II) preconcentration in food samples. All carbon-based membrane exhibits good stability under extraction process. Membrane extraction with large enrichment factor enables the use of large sample volumes. Abstract: Here, a solid/liquid phase extraction mode was used for the preconcentration of Pb(II) in water and food samples through a biomass reinforced graphene oxide (BGO) membrane. Taking advantage of the two modes, the synergistic effect of BGO membrane (solid extraction) and organic solvent (liquid extraction) enhances the extraction efficiency toward target ion. In detail, the effect of composition parameters in BGO membrane and experiment conditions such as pH, eluent types, elution time and sample volume were optimized, as well as shows no obvious interference toward different competing ions. Under the optimal experiment conditions, the limit of detection, precision as RSD% of this method were found to be 0.84 μg L −1 and 4.65%, respectively. Moreover, the large enrichment factor of BGO membrane demonstrates the applicability of the use of large sample volumes. Furthermore, the method was successfully verified by analyzing spiked Pb(II) in water and food samples.